2016
DOI: 10.1071/sh15189
|View full text |Cite
|
Sign up to set email alerts
|

What qualities of long-acting reversible contraception do women perceive as desirable or undesirable? A systematic review

Abstract: Little research examining qualities of contraception that make them attractive or unattractive to users, particularly young women, exists. The aim of this study is to systemically review the evidence regarding desirable and undesirable qualities of long-acting reversible contraception (LARC), including intrauterine devices, the implant and the injection, as perceived by women. Five electronic databases were searched in May 2015 using terms related to LARC and method preference or decision-making. Studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 50 publications
0
32
1
Order By: Relevance
“…Although a systematic review by Coombe et al 34 found that longevity was reported by women as one of the top positive characteristics of IUC, our research shows that the long-acting nature of the method is not seen as an advantage by all women. This is a finding echoed in previous research 8 12.…”
Section: Discussioncontrasting
confidence: 74%
“…Although a systematic review by Coombe et al 34 found that longevity was reported by women as one of the top positive characteristics of IUC, our research shows that the long-acting nature of the method is not seen as an advantage by all women. This is a finding echoed in previous research 8 12.…”
Section: Discussioncontrasting
confidence: 74%
“…The most commonly cited negative aspects attributed to LARC are irregular bleeding, painful insertion/removal, weight gain, and general aversion to having a device inserted into the body. [6]…”
Section: Introductionmentioning
confidence: 99%
“…Some Australian women describe the implant as weird, bizarre, creepy, or even akin to being microchipped . There are also misconceptions about risks and feelings that LARC methods would only be appropriate in a later phase of their lives . Some fear needles or pain .…”
Section: Disclosure Of Interestsmentioning
confidence: 99%
“…In this regard, LARC methods are remarkable agents as they provide high effectiveness without the permanency of sterilisation. Many women value the ‘fit and forget’ property that gives them peace of mind . The contribution that LARC has made to allowing women to play a full part in society cannot be overstated.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation